Asymmetric Effects of Economic Policy Uncertainty on the Demand for Money in India - Murad, Woahid; Salim, Ruhul; Kibria, Golam (Springer, 2021)
This study aims to extend the conventional money demand function by including the economic policy uncertainty (EPU) index in the Indian money demand function. The rest of the determinants are income, interest rate, infation rate, and exchange rate. Both symmetric and asymmetric efects of uncertainty are estimated covering the period 2003M1–2018M4. The linear ARDL bounds testing approach shows that uncertainty has a signifcant efect on narrow money in the short run. At the same time, the asymmetric nonlinear framework supports the short-run asymmetric efect of uncertainty on both narrow and broad money. More precisely, the policy uncertainty is a short-run phenomenon for the Indian money demand function. However, both linear and nonlinear models yield a stable demand for money in India regardless of narrow money or broad money. Hence, the monetary policy can be initiated to tune the Indian economy.